The Relationship Between Cotton Bud Use and The Incidence of Cerumen Impaction Among Patients at The ENT Polyclinic of PKU Muhammadiyah Bantul Hospital - Nadila; Firmansyah, Rizky; Ariani, Rizka (Universitas Ahmad Dahlan, 2025)
Cotton buds are commonly used to clean ears, although improper use can be harmful to ear health by causing cerumen impaction. Cerumen is a natural substance that normally exits the ear canal on its own but can accumulate due to cotton bud use, leading to hearing problems. This study aims to examine the relationship between cotton bud use and the incidence of cerumen impaction in patients at the ENT Polyclinic of PKU Muhammadiyah Hospital, Bantul, considering the high prevalence of this condition in Indonesia. This research used a cross-sectional design and collected data through questionnaires from 65 patients at the ENT clinic. The data were analyzed using SPSS 25 with chi-square and Fisher’s exact tests. Results showed that 86.2% of patients used cotton buds up to 2/3 of the inner ear canal. There was no significant relationship between the depth of cotton bud use and the incidence of cerumen impaction (p = 0.483). However, there was a significant relationship between the frequency of cotton bud use (> 1 time a week) and cerumen impaction in both ears (p = 0.032). Patients who frequently used cotton buds had a higher incidence of cerumen impaction compared to those who used them rarely. In conclusion, there is a relationship between the frequency of cotton bud use and the incidence of cerumen impaction.